KONTRIBUSI IKATAN PENDIDIK QUR’AN DAN LEMBAGA PENGEMBANGAN TILAWATIL QUR’AN DALAM MENINGKATKAN KEMAMPUAN MENGAJAR BACA TULIS AL-QURAN GURU MADRASAH DINIYAH - Wargono Wargono; hunainah hunainah (QATHRUNÂ, 2022)
In an effort to improve the teaching skills of reading and writing Al-Qur’an madrasah teachers in the City of Serang, researchers conducted research at Madrasah Diniyah Mu'awanatusy Syubban, Kaujon Village, Serang City and Madrasah Diniyah Ath-Thalabah, Sumur Pecung Village, Serang City of Serang. The objectives of this study are (1). To find out the contribution of the Qur’an Educators Association to the teaching ability of BTQ teachers in Serang City. (2). To find out the contribution of the Tilawatil Qur’an Development Institute to the teaching ability of BTQ madrasah teachers in Serang City. (3). This is to find out the impact of IPQ and LPTQ coaching on the teaching ability of BTQ teachers in Madrasah in Serang City of Serang. The results of the research and discussion are (1). Training and coaching at Madrasah Diniyah Mu'awanatusy Syubban in person or face to face, while training and coaching at Madrasah Mu'awanatusy Syubban are virtual (2). The training and coaching of the IPQ and LPQ in Serang City, which was held at Madrasah Diniyah Mu'awanatusy Syubban, had only officially been held once. But independently the teachers at Madrasah Diniyah Mu'awanatusy Syubban often conduct training from the institution that is part of the IPQ, namely BKPAKSI, using the Tilawati method. Meanwhile, the training and coaching that was conducted at Madrasah Diniyah Ath-Thalabah, Sumur Pecung Village, Serang City, was held for the first time. (3). The impact that arises from the training and coaching carried out by IPQ and LPTQ Serang City, including the establishment of a unidirectional relationship between Madrasahs and IPQ, LPTQ, and the Ministry of Religion of Serang City, higher quality Madrasas, increased insight, skills, and knowledge of the Madrasah and the teachers. The training and coaching make teachers and students more enthusiastic and creative in learning, the learning atmosphere is more comfortable and enjoyable because it uses a well-known dynamic song, namely the rost song in reading every material in the learning that is being carried out. The conclusion from this research is that in order to improve the teaching ability of teachers BTQ Madrasah in the City of Serang, then the IPQ and LPTQ the City of Serang is committed to conduct intensive coaching so that all teachers BTQ Madrasah in the City of Serang can coached and trained in a systematic way.